1974
DOI: 10.1677/joe.0.0620109
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Metabolism of Tritiated Oestradiol and Oestrone by Human Endometrial and Myometrial Tissue in Vitro

Abstract: Human endometrial and myometrial tissues were incubated in vitro with [3H]oestradiol-17\g=b\ and [3H]oestrone to study the uptake and interconversion of these two steroids by the tissues. Endometrial tissue displayed a higher capacity for oestrogen interconversion than myometrial tissue and the oxidation of oestradiol-17\g=b\ to oestrone was favoured, rather than the reverse reaction. A greater degree of oxidation was found in tissue taken from uteri in the secretory phase than in the proliferative phase. A st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Receptors for both E and P have been identified in leiomyomata (3). In addition to ovarian E, some investigators have shown that leiomyoma tissues are a source of E. Leiomyoma cells express an E synthetase as well as aromatase and convert circulating androgens to E (4)(5)(6)(7)(8)(9). Estrogen secreted by leiomyomata tissue may reach a sufficient concentration within the local compartment to support its own growth, allowing independence from ovarian E (10).…”
mentioning
confidence: 99%
“…Receptors for both E and P have been identified in leiomyomata (3). In addition to ovarian E, some investigators have shown that leiomyoma tissues are a source of E. Leiomyoma cells express an E synthetase as well as aromatase and convert circulating androgens to E (4)(5)(6)(7)(8)(9). Estrogen secreted by leiomyomata tissue may reach a sufficient concentration within the local compartment to support its own growth, allowing independence from ovarian E (10).…”
mentioning
confidence: 99%
“…In addition, the levels of both recep tors followed the same changes throughout the cycle as those in the endometrium and myometrium [3,4,12,[21][22][23][24], Previous measurements of the cytosolic levels of the estradiol and progesteroene re ceptors in relation to the levels of these receptors in the corresponding endometrium and myometrium yielded conflicting results [21,23,25,26], However, the results of recent studies [3,4,27], and the present report indicated that the levels of both recep tors are higher in the LM as compared with the tumor-bearing myometrium.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that leiomyoma tissues are a source of estrogen. Leiomyoma cells express an estrogen synthetase as well as aromatase and convert circulating androgens to estrogen [30,32,33]. Estrogen secreted by leiomyoma tissue may reach a sufficient concentration within the local compartment to support its own growth, allowing independence from ovarian estrogen [34,35].…”
Section: Aromatase Inhibitorsmentioning
confidence: 99%